Does Personal Attitude Play a Role in Building Entrepreneurial Intentions? Studies On Students of the State University of Jakarta - Fawaz Akbar Ramadhan Budiman; Yufiarti Yufiarti (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of personal attitude on entrepreneurial intentions in students at the State University of Jakarta. Personal attitude is one of the important factors that is believed to affect a person's intention to engage in entrepreneurial activities. This study uses a quantitative approach with a survey method, involving students of the State University of Jakarta as respondents. Data collection is carried out through questionnaires that have been tested for validity and reliability. The results of the analysis showed that personal attitude had a significant influence on the entrepreneurial intention of students at the State University of Jakarta, amounting to 68.2%. These findings indicate that a positive attitude towards entrepreneurship contributes to an increase in students' intention to start a business. This research provides implications for educational institutions to improve programs that can strengthen students' positive attitudes towards entrepreneurship as one of the efforts to support the development of young entrepreneurs.